2014
DOI: 10.1007/s00213-014-3772-2
|View full text |Cite
|
Sign up to set email alerts
|

Episodic foresight deficits in long-term opiate users

Abstract: These data provide important preliminary evidence that episodic foresight might be particularly susceptible to the neurocognitive effects of opiate use, as the difficulties identified were not secondary to more general executive control or episodic memory impairment. Because a number of widely used relapse prevention protocols require the ability to mentally project into the future, these data have potentially important practical implications in relation to the treatment of substance dependence disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…This network has been implicated in episodic prospection and construction processes (Schacter et al, 2012). In line with previous behavioral research (Wiehler et al, 2015), but distinct from findings in long-term opiate users (Mercuri et al, 2015), we found no evidence for an impairment of episodic future thinking in pathological gamblers and no evidence for an impairment in the underlying neuronal mechanisms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This network has been implicated in episodic prospection and construction processes (Schacter et al, 2012). In line with previous behavioral research (Wiehler et al, 2015), but distinct from findings in long-term opiate users (Mercuri et al, 2015), we found no evidence for an impairment of episodic future thinking in pathological gamblers and no evidence for an impairment in the underlying neuronal mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…First, an intact baseline episodic future thinking is a requirement for these putative interactions between episodic future thinking and temporal discounting. While opioid addicts might be impaired in episodic future thinking (Mercuri et al, 2015), episodic future thinking is unaffected and unrelated to baseline temporal discounting in pathological gambling (Wiehler et al, 2015). In this previous study, patients imagined possible future events following a cue.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study to date has investigated the capacity for episodic foresight in the context of chronic opiate use, and as noted, the results showed that the ability to mentally travel forward in time is disrupted (Mercuri et al ., ). This finding aligns with neuroimaging evidence that has consistently shown chronic opiate use to be associated with abnormalities in temporal regions including the MTL (Cheng et al ., ; Fu et al ., ; Liu et al ., ; Wang et al ., ), the neural regions that have been most strongly linked to episodic foresight (Schacter & Addis, ).…”
Section: Introductionmentioning
confidence: 97%
“…Chronic opiate use is associated with poor functional, social, and economic outcomes (Hser, Hoffman, Grella, & Anglin, ; Villeux, Colvin, Anderson, York, & Heinz, ), and relapse following rehabilitation is common (Smyth, Barry, Keenan, & Ducray, ). A recent study of long‐term opiate users identified impairment in this group on a key cognitive ability, episodic foresight (Mercuri et al ., ), that may help explain these functional difficulties and high relapse rates. Episodic foresight refers to the ability to mentally project oneself into the future and pre‐experience events (Atance & O'Neill, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation